SSI, labor supply, and migration - David Neumark; Elizabeth T. Powers (Institute for the Study of Labor (IZA), 2005)
The Supplemental Security Income (SSI) program in the United States creates incentives for potential aged recipients to reduce labor supply prior to becoming eligible, and our past research finds that older men likely to be eligible for SSI at age 65 reduce their labor supply in the years immediately before the age of eligibility. However, given the dramatic supplementation of SSI benefits in some states, a migration response to these benefits cannot be dismissed, and migration that is associated with SSI benefits can lead to bias in estimates of the effects of SSI benefits on labor supply; depending on retirement and migration behavior, the disincentive effects can be overstated or understated. Migration responses to SSI benefits are also important in their own right, as another instance of the potential problem of welfare magnets. We fail to find any statistically significant evidence that older individuals likely to be eligible for SSI in the near future, or already eligible for SSI, are more likely to move from low benefit to high benefit states. These findings are robust to the use of a number of different comparison groups to try to capture the state-to-state migration patterns that exist independently of a response to SSI. The evidence indicates that labor supply disincentive effects of SSI do not stem from migration behavior that could, in principle, spuriously generate these findings.
Keywords: J14; J22; I38; R23; 330; SSI; labor supply; migration